The effect of e-learning media on the improvement of learning outcomes in the Vehicle Body Construction course for students of the Department Automotive Faculty of Engineering UNP - Hendra Dani Saputra; Dedi Setiawan; Muslim Muslim; Bahrul Amin; Rido Putra (invotek, 2021)
Research-based on data on the low student learning outcomes. Internal and external factors cause little learning outcomes. Previous research has concluded that valid and practical E-learning media will streamline the learning process. Research focuses on one of the external factors that cause low learning outcomes. E-learning media is an external factor that is the focus of research. This study aims to analyze the E-learning media on learning outcomes. The analysis results will provide an overview of E-learning media's influence on improving learning outcomes. The increase in learning outcomes in the form of post-test scores on E-learning media is carried out. This research is an experimental study with a randomized control-group post-test only design, where the research subjects were students majoring in automotive engineering. Samples were taken randomly using data collection in data test for student learning outcomes in the Automotive Engineering Department, Faculty of Engineering, UNP. The collected learning outcome test data were analyzed according to the data analysis process, and the results were tested to examine E-learning media's effect on improving student learning outcomes. The test results showed an increase in learning outcomes by 25.33%. The research concludes that E-learning media has no significant impact on learning outcomes.